O co-relato Mallarmé / Haroldo de Campos: o mito moderno em "Um lance de dados" - Bento, Sérgio Guilherme Cabral (2008)
In its modern concept, the myth is a behavioral paradigm, a symbolical model of an external reference. Based on that, this paper defends that the poem A throw of the dice , by Stéphane Mallarmé, acquires such mythical status, either by its cosmogonical nature which is commonly ignored by the critics -, or by its formalistic innovations reason why it got so acclaimed. Due to that, it suffered during the XX century a mythification process, in which it was promoted to be elected as one of the inspirational sources of recent and contemporary poetry. So that such approach was possible, the study was delimitated to a comparison between the proposed text to its re-creation in Portuguese, done by Haroldo de Campos. This dialogue translation / original not only updates the myth A throw of the dice by the ritualistic value the translation process has, but also allows the analysis to get closer to the current times. As an instrument for this exegesis, the Gestalt theories principles of form organization; concept of whole , which is not a mere addition of its parts, but has a unique quality aggregated; and the phenomenon of psiconeural correlation in human visual perception ensure that the poem will be considered in its totality, as a verbal, visual and sound entity. In short, it has been concluded that the poem A throw of the dice is a tale of the (re-) creation of the Universe, the human being and the Art, not under the guidance of a divine power, but generated by the human thinking, key factor in the new illuminist bourgeois society in Modern Age. The modern myth is formed